2009
DOI: 10.1016/s0873-2159(15)30145-8
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da inflamação das vias aéreas. Vias áreas superiores e compartimento broncopulmonar

Abstract: It is done a review of evaluation methods of the inflammation in upper airways and bronchi used for diagnosis, therapeutic approach and prognosis of pathologies like rhinosinusitis and asthma. It is also analysed methods that supply relevant information of inflammation in COPD. The chronic inflammation of the airways is associated to respiratory distress, obstruction in basal lung function tests and to bronchial and nasal hyperreactivity. Computerized tomography informs about lumen dimensions, bronchial walls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Pneumonia can be identified more easily by detecting odors [20]. Analysis of Volatile Organic Compounds (VOCs) in exhaled breath, and thermal desorption with gas chromatography coupled to mass spectrometry (TD-GC-MS) can be used to identify VOCs and the causative pathogen in patients suspected of VAP [21,22,23]. However, researchers have found that a variety of bacteria such as Klebsiella pneumoniae, Acinetobacter baumanii, Escherichia coli, Staphylococcus aureus , and Pseudomonas aeruginosa contribute to VAP, and it is very crucial to find a way to recognize these different types.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia can be identified more easily by detecting odors [20]. Analysis of Volatile Organic Compounds (VOCs) in exhaled breath, and thermal desorption with gas chromatography coupled to mass spectrometry (TD-GC-MS) can be used to identify VOCs and the causative pathogen in patients suspected of VAP [21,22,23]. However, researchers have found that a variety of bacteria such as Klebsiella pneumoniae, Acinetobacter baumanii, Escherichia coli, Staphylococcus aureus , and Pseudomonas aeruginosa contribute to VAP, and it is very crucial to find a way to recognize these different types.…”
Section: Introductionmentioning
confidence: 99%